Biogeochemical cycling of nutrients and trace metals in anoxic freshwater sediments of the Neckar River, Germany - Song, Yigang; Müller, German (Marine and freshwater research, 1995)
Pore-water components (SO42-, Fe2+, Mn2+), including nutrients (NH4+:, NO3-, PO43-), alkalinity and pH were determined at three sites in the Neckar River. Sequential extraction procedures and trace metals in both pore waters and sediments are reported in order to evaluate the mobility of trace metals in contaminated sediments. The results show that the mineralization of organic matter plays an important role in the cycling of nutrients and trace metals. Pore-water profiles (Zn, Cu, Pb, Cd) suggest that the element maximums at the sediment-water interface are caused by the decomposition of biomass. Low concentrations of dissolved Zn, Cu, Pb and Cd in the anoxic sediments can be explained by a sharp decrease of SO42- in pore water concomitant with HS- production. This leads to the formation of highly insoluble metal sulfides. Solubility calculations show that the sediments act as a sink for trace metals with respect to trace metal sulfides. The organic/sulfidic-bound fraction accounts for 64-81% of Cd in the sediment cores, 36-67% of Pb and 51-69% of Cu. In contrast, Cr in pore water increases with depth because of its release from Fe/Mn oxides. NH4+ and PO43- are also released into the pore water owing to the mineralization of organic matter. No significant fluxes of NH4+ and PO43- into overlying water were found because of the existence of an oxic surface layer.